Evaluating Character Education Implementation in Elementary Schools : A Kirkpatrick Model Perspective - Yuliana, Lastri; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Jurnal Paedagogy, 2025)
This study aims to evaluate the implementation of character education at SDN 015 Balikpapan Selatan using the Kirkpatrick Evaluation Model, which comprises four levels: reaction, learning, behavior, and result. The research was motivated by the need to reinforce character values after the COVID-19 pandemic, which led to a decline in students' positive behaviors due to prolonged online learning. A mixed-method approach with an explanatory sequential design was employed. Quantitative data were collected through questionnaires from 89 students (grades II-VI), while qualitative data were obtained through interviews, observations, and document analysis. The data analysis employed a simple quantitative descriptive approach using Microsoft Excel to calculate percentage scores and categorize them into five levels (very high, high, moderate, low, and very low) based on the Kirkpatrick evaluation model. Qualitative data from interviews, observations, and documents were narratively integrated to support and enrich the findings. The findings revealed that the reaction stage achieved an average score of 90.87%, the learning stage 88.24%, and the behavior stage 88.07%, all within the very high category. At the result stage, character education was found to have a positive long-term impact on students' learning motivation, social behaviors, and engagement both at school and at home. The program successfully fostered student discipline, independence, empathy, and moral conduct. However, challenges remain in achieving consistent internalization of character values, particularly outside the school environment. Overall, the study concludes that character education at SDN 015 Balikpapan has been effectively implemented and significantly contributes to shaping students' character, although ongoing improvement is needed through more collaborative strategies involving both schools and parents.